Legal Responsibilities of Members of the Makassar City Regional People's Representative Council (DPRD) to their Constituents in the Electoral District - Arif, Wahyudi; Moenta, Andi Pangerang; Hasrul, Muh. (Fakultas Syariah INSURI Ponorogo, 2023)
This research aims to examine the legal responsibilities of members of the Makassar City Regional People's Representative Council (DPRD) towards their constituents in the electoral district, as well as identifying the inhibiting factors faced by DPRD members in fulfilling their responsibilities towards constituents in their respective electoral areas. Employing an empirical legal research approach, the study seeks to comprehend the actual application of law and explore its functionality within the societal context, conceptualizing it as a social phenomenon influenced by various social variables. The study was conducted at the Makassar City DPRD office. Data collection methods encompassed interviews, observations, and literature review. The acquired data underwent qualitative analysis and descriptive elucidation. The research findings reveal that a significant number of elected representatives do not demonstrate expected behaviors, resulting in a considerable deficiency in their role of fulfilling responsibilities towards constituents in the electoral district. These limitations are attributed to several inhibiting factors, including inadequate community participation, limited financial allocation from the Makassar city government, constraints in meeting times and facilities, and the diverse and busy schedules of both DPRD members and constituents.